2010
DOI: 10.1590/s1519-69842010000400004
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic efficiency of Clusia arrudae leaf tissue with and without Cecidomyiidae galls

Abstract: Leaf galls induced by a still undescribed new species of Cecidomyiidae (Diptera) are frequent on leaves of Clusia arrudae Planchon & Tirana (Clusiaceae) in the rupestrian fields at 1400 m a.s.l. in Serra do Cipó, Minas Gerais, Brazil. Galls were 7.1 ± 0.7 mm in diameter, one chambered with only one larva inside. Gall tissue is green and soft. Assessments of photosynthetic capacity using chlorophyll-a fluorescence measurements revealed that photosynthetic performance of gall tissue and healthy leaf tissue were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 35 publications
0
14
0
2
Order By: Relevance
“…Gall-inducing insects are considered the most sophisticated and capable due to their ability to manipulate the host plants for their benefit (Abrahamson & Weis 1997, Shorthouse et al 2005, Fernandes et al 2010). Galls could be considered to be an extension of the inductor phenotype, since their morphological characteristics depend on the inductor genotype as well as on environmental factors such as heat, humidity, and soil (Weis et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Gall-inducing insects are considered the most sophisticated and capable due to their ability to manipulate the host plants for their benefit (Abrahamson & Weis 1997, Shorthouse et al 2005, Fernandes et al 2010). Galls could be considered to be an extension of the inductor phenotype, since their morphological characteristics depend on the inductor genotype as well as on environmental factors such as heat, humidity, and soil (Weis et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…At plant growth stage R3 and R4 aphid population increased and this collided with cowpea plant having succulent pods and vining nodes [ Table-3]. Fernandes, et al [26] found that higher aphid population feeding was distributed more on the pods and nodes than on the leaves mainly because of high nitrogen concentration. Generally, this study has revealed that eventhough the nitrate content in the sewage water was at significant amounts, it did not influence or affect the population growth of aphids.…”
Section: Effect Of Treatments Levels On Population Growth Of Cowpea Amentioning
confidence: 99%
“…Plants belonging to this genus are known for their many biological activities, such as antibacterial, antioxidant, antitumor, antimicrobial and anti-inflammatory activities (Gustafson et al, 1992;Iinuma et al, 1996;Cruz and Texeira, 2004). Species of Clusia are targets of galls in leaves by herbivory (Santos-Mendonça et al, 2007;Constantino et al, 2009;Fernandes et al, 2010). The insect inducing galls Clusiamyia nitida (Diptera, Cecidomyiidae) often infests the shrub Clusia lanceolata (Clusiaceae) in the Neotropical sand dunes vegetation in Rio de Janeiro State (Constantino et al, 2009).…”
Section: Introductionmentioning
confidence: 99%